INCREASING SOIL FERTILITY AND POROSITY THROUGH FERTILIZATION - Ikromov, Ravshan Abdurasul o‘g‘li; Jo‘rayeva, Shaxrizoda Imom qizi (Educational Research in Universal Sciences, 2024)
The article likely discusses various fertilization techniques aimed at enhancing soil fertility. This could include the application of organic or synthetic fertilizers, the timing and method of application, and the specific nutrients targeted for improved soil health. The focus is likely on how fertilization impacts soil porosity, elucidating the mechanisms through which added nutrients contribute to the development or maintenance of porous soil structures. It may explore the role of fertilization in promoting microbial activity and organic matter decomposition, key contributors to soil porosity